Assessment of impact of small group teaching among students in community medicine - Ranabir Pal; Sumit Kar; Forhad Akhtar Zaman; Dilip Kumar Jha; Shrayan Pal (Wolters Kluwer Medknow Publications, 2012)
Background: We conducted a study to assess the impact of small group teaching (SGT) among students by feedback analysis to identify intricacy so that learning can be facilitated. Materials and Methods: This cross-sectional study was undertaken among 182 MBBS students studying at a teaching hospital at Gangtok. Students were provided with a questionnaire following an assignment on a scheduled topic. Students were asked to provide feedback on the modes of teaching-learning practiced in community medicine with the parameters of evaluation including assessment of presentation by faculty member in reference to relevance, sequencing, depth, interaction, etc., to the overall rating of presentations in different teaching-learning methods. Results: The faculty members were on the positive evaluation by the students in the SGT, which was preferred over "lectures" as the teaching-learning methods. Among SGTs "tutorials" were graded better than "practical," "seminar" and "field posting" on the basis of longer duration at a stretch. Among the parameters for evaluation, relevance, depth, and interaction in regard to scheduled topic of presentations, the rating was significantly higher in SGT than different other teaching-learning methods. Largely the students noted that the time devoted and number of hours/sessions allotted for each topic was adequate. Conclusion: All forms of SGT were on the positive appraisal by the students on their learning experience and were considered as a comprehensive tool for in-depth teacher-student interaction.